Instillation of The Value of Caring for the Environment at Elementary Students in Pamekasan, Indonesia - Muhammad Arfan Mu’ammar; Moh. Badri (The Indonesian Institute of Science and Technology Research, 2022)
It is possible to develop an effective green society through environmental education in schools. Schools play a special role as places of learning. Schools can help students understand the impact of human behaviour on the planet. The Adiwiyata program is designed to create school citizens who are responsible for environmental protection and management through superior school operations to support sustainable development. The Adiwiyata program combines learning and behaviour to provide an effective way to change behavior. Madrasah Ibtidaiyah Mambaul Ulum I Bata-Bata Panaan Palengaan Pamekasan is expected to be a mediator of change in the community around the school. Schools need to be role models for creating a healthy and comfortable environment, as well as being role models for creating school citizens who care and are environmentally friendly. In this case, the school community is expected to be a role model and convey the nature of their concern for the environment to the surrounding community. The purpose of this research was the efforts of Madrasah Ibtidaiyah Mambaul Ulum Bata-Bata Panan Palengan Pamekasan in creating environmentally friendly students by building character. Therefore, this research was a descriptive research, namely research that tried to explain a certain phenomenon, event, or event by using qualitative data. The data analysis used an interactive data analysis model. Namely through interviews, observation, and documentation. Based on the research here, the researcher concluded that self-development programs, disciplined learning processes, motivate the importance of cleanliness in the classroom and in the school environment, development of school environment health, and school culture. Inhibiting factor in MI. Mambaul Ulum Bata-Bata was a facility that breaks down quickly. Inhibiting factor in MI. Mambaul Ulum Bata-Bata were: limited land and finances.